An appraisal of dwell sensitive fatigue in Ti-6Al-4V and the governing role of inhomogeneous micro-texture. (June 2023) - Li, J.; Davies, H.M.; Fox, K.; Mulyadi, M.; Glavicic, M.G.; Bache, M.R.
Highlights: Characterisation of a proprietary Ti-6Al-4V fan disc forging has illustrated the presence of "macrozones" or "microstructurally textured regions (MTRs)" LCF tests have illustrated a debit in fatigue strength if a hold of two minutes is imposed at the peak of the loading waveform. EBSD can be applied to metallographic polished sections or directly from the fracture surface of failed fatigue specimens to identify MTRs. Ti-6Al-4V should be considered as "dwell sensitive" when containing MTRs of the scale investigated during the present study. Abstract: The fact that the α/β titanium alloy Ti-6Al-4V is sensitive to cold dwell loading regimes has recently been endorsed by a combination of evidence gathered from fatigue studies performed on laboratory scale specimens and the findings of a failure investigation into an in-service fan disc failure. This work confirms that Ti-6Al-4V can demonstrate dwell characteristics under fatigue loading, subject to the microstructure and micro-texture developed during thermo-mechanical processing. Additional fatigue data are presented to support this conclusion, together with detailed metallographic and crystallographic characterisation to identify the factors controlling inhomogeneous strength, stress distribution and the crack initiation process on the micro to macro scale.